Functional and biochemical analysis of the N-terminal domain of phytochrome A - Mateos, Julieta Lisa (2006)
Phytochrome A (phyA) is a versatile plant photoreceptor that mediates responses to brief light exposures (very low fluence responses, VLFR) as well as to prolonged irradiation (high irradiance responses, HIR). We identified the phyA-303 mutant allele of Arabidopsis thaliana bearing an R384K substitution in the GAF subdomain of the N-terminal half of phyA. phyA-303 showed reduced phyA spectral activity, almost normal VLFR, and severely impaired HIR. Recombinant N-terminal half oat of PHYA bearing the phyA-303 mutation showed poor incorporation of chromophore in vitro, despite the predicted relatively long distance (>13 Å) between the mutation and the closest ring of the chromophore. Fusion proteins bearing the N-terminal domain of oat phyA, β-glucuronidase, green fluorescent protein, and a nuclear localization signal showed physiological activity in darkness and mediated VLFR but not HIR. At equal protein levels, the phyA-303 mutation caused slightly less activity than the fusions containing the wild-type sequence. Taken together, these studies highlight the role of the N-terminal domain of phyA in signaling and of distant residues of the GAF subdomain in the regulation of phytochrome bilin-lyase activity.